Fabrication and thermo stability of the SnO2/Ag/SnO2 tri-layer transparent conductor deposited by magnetic sputtering. Issue 3 (1st February 2021) - Wang, Wei; Wei, Xiaojun; Wang, Chuanshen; Zhou, Wencai; Zhu, Bailin; Wang, Chongjie; Liu, Linfei
Abstract: Using the magnetic sputtering technique, the SnO2 /Ag/SnO2 tri-layer transparent films were fabricated on float glasses successfully. Compared with the commercial FTO (F-doped SnO2 ) film, the SnO2 /Ag/SnO2 tri-layer films have higher visible-light transmittance and better conductivity. The total thickness of the SnO2 /Ag/SnO2 films is one third of the commercial FTO film leading to the high visible-light transmittance. The high carrier concentration of the SnO2 /Ag/SnO2 films contributes to the tri-layer films' low resistivity. In addition, to further improve the performance of the SnO2 /Ag/SnO2 tri-layer films, samples were annealed under different temperatures. The results illustrate that the lowest sheet resistance (5.92 Ω/sq) and the highest visible-light transmittance (87.0%) were obtained after annealing at 200 °C. Furthermore, the thermal stability of the films could be enhanced by a multi-step annealing process due to the recrystallization effect.